The role of p38-MAPKs in mouse preimplantation embryonic development: Regulating translation towards blastocyst maturation and lineage specification. - Bora, Pablo (Jihočeská univerzita, 2021)
Preimplantation embryonic development in mammals is the period from fertilisation of the gametes to implantation of the blastocyst embryo in to the uterine walls, poised for post-implantation foetal development. This is a 5-day long process in mouse, and encompasses signalling and gene regulatory mechanisms, metabolic, cellular and organellar structural transformations, resulting in progressively reduced cellular potency and three distinct lineages. The outer and inner cells around the 16-32-cell stage are designated as the trophectoderm (TE) and the inner cell mass (ICM), respectively. 32-cell stage onwards, the ICM further differentiates to the pluripotent epiblast (EPI) and epithelial, multi-potent primitive endoderm (PrE). TE and PrE generates the extra-embryonic tissues, placenta and yolk sac, respectively, and EPI forms the embryo proper. Typical generation of extra-embryonic cells and tissues is indispensable for normal embryonic development. p38-MAPKs, a family of four stress-activated kinases, play crucial roles throughout early development, though mechanistic understanding is limited. Studies within this thesis, building upon previous work, reports on the requirement of functional p38-MAPKs towards a translational landscape conducive for developmental cell fate specification and blastocyst maturation (E3.5 to E4.5). Phosphoproteomics, transcriptomics and experimental analysis revealed possible complications in ribosome biogenesis and an attenuated translational landscape upon inhibition of p38-MAPK activity, likely due to impaired function and localisation of downstream effectors. Some of the effectors identified, such as DDX21, MYBBP1A, and GNL3, are involved in rRNA transcription and processing, with null mutants demonstrating lethality prior to implantation. Similar to p38-MAPK inhibition, loss-of-function analysis of the effectors also resulted in fewer cells, particularly of GATA4 expressing PrE lineage. Experiments to identify the position of p38-MAPK in cell fate specifying signalling cascade revealed it as independent of the quintessential FGF4-FGFR-MEK/ERK pathway, but upstream of mTOR and potentially functional in the recently described FGFR2/PDGFRa-PI3K-mTOR pathway mediating PrE survival. p38-MAPK was also found to be functional in ameliorating amino acid deprivation induced oxidative stress during blastocyst maturation, by facilitating gene expression of anti-oxidant enzymes.
The role of p38-MAPKs in mouse preimplantation embryonic development:Regulating translation towards blastocyst maturation and lineage specification.